A WEBSITE-BASED INFORMATION SYSTEM DEVELOPMENT FOR APPLYING TEMPORARY AIRPORT PASS REGISTRATION - Adilia Parmono, Zalzariana; Parjan, Parjan; Andayani, Thursina; Azzahra, Vania Nadhifa; Akaike, Hideo (Journal of Airport Engineering Technology (JAET), 2024)
Pass visitor is an entry permit used by guests (visitors) who carry out visits or activities at the airport, and the management and registration process for applying is still done manually. This research aims to build a website-based application for registered pass visitors and conduct black box testing. The research and development (R&D) method uses the System Life Development Cycle (SDLC) technique with waterfall as a development model that involves analysis, design, implementation, and testing. Data collection by conducting observation and document analysis. The result is a website-based application that is designed using Google Apps Script. This application has been validated by a media design expert with a validation result of 82.10% and a material expert with a validation result of 86.25% with the category "Very Feasible" and tested using Black box testing. The website information system for applying for Pass visitor registration can be used on various platforms and runs flexibly anywhere and anytime online. By conducting this system, airport management can achieve time flexibility in the registration process and convenience in managing pass visitor data storage. This system simplifies the registration process to improve the quality and security of the airport.